2020
DOI: 10.1177/0959683620972768
|View full text |Cite
|
Sign up to set email alerts
|

Multi-profile fine-resolution palynology of Late Mesolithic to Bronze Age peat at Cat Stones, Rishworth Moor, Central Pennines, UK

Abstract: Palynological data from three radiocarbon dated peat profiles at Rishworth Moor in the Pennine hills of northern England provide a record of vegetation change and human impacts in the Late Mesolithic, Neolithic and Bronze Age periods. All three cultures have archaeological sites present in the vicinity, with Late Mesolithic sites by far the most abundant, comprising mainly very late assemblages dominated by ‘rod’-shaped microliths. Pollen evidence of vegetation disturbance occurs during all three archaeologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
(167 reference statements)
0
2
0
Order By: Relevance
“…Lynch (1981) recorded Hordeum type grains at Cashelkeelty in southwest Ireland. Some studies have applied morphology criteria to cereal-type grains, primarily Hordeum , from the beginning of this period in Britain (Albert et al, 2021) and northern Europe (Alenius et al, 2017; Poska and Saarse, 2006; Wieckowska et al, 2012) and concluded that they do represent Hordeum rather than any wild grass, presumably procured by hunter-gatherers during an ‘availability phase’ (Zvelebil and Rowley-Conwy, 1984) before the advent of the Neolithic, or by small groups of pioneer settlers with at least a partly ‘Neolithic’ resource base. As all of these studies separated Hordeum from Glyceria on morphological criteria, it seems that such records from this early time period must be accepted, or at least given serious consideration, even in these more peripheral areas of Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lynch (1981) recorded Hordeum type grains at Cashelkeelty in southwest Ireland. Some studies have applied morphology criteria to cereal-type grains, primarily Hordeum , from the beginning of this period in Britain (Albert et al, 2021) and northern Europe (Alenius et al, 2017; Poska and Saarse, 2006; Wieckowska et al, 2012) and concluded that they do represent Hordeum rather than any wild grass, presumably procured by hunter-gatherers during an ‘availability phase’ (Zvelebil and Rowley-Conwy, 1984) before the advent of the Neolithic, or by small groups of pioneer settlers with at least a partly ‘Neolithic’ resource base. As all of these studies separated Hordeum from Glyceria on morphological criteria, it seems that such records from this early time period must be accepted, or at least given serious consideration, even in these more peripheral areas of Europe.…”
Section: Discussionmentioning
confidence: 99%
“…BP (Griffiths, 2022; Gron et al, 2018; Warren, 2013; Zvelebil, 1994), although much shorter than in mainland Europe and with little genetic transfer (Mithen, 2022). ‘Terminal Mesolithic’ rod microlith sites in northern England, for example, date right up to the end the Mesolithic-Neolithic transition period and so overlap with Neolithic archaeological sites in the region (Albert et al, 2021; Albert and Innes, 2015; Griffiths, 2014; Spikins, 2002). The respective impacts of the late Mesolithic and the earliest Neolithic on the landscape might have been of a similar scale and difficult to distinguish, but a means of detecting the initial Neolithic might be through changes in human ecology and vegetation disturbance which, although probably subtle and spatially restricted, altered ecosystems (Welinder, 1983) and vegetation patterns (Caseldine and Fyfe, 2006; Woodbridge et al, 2014).…”
Section: Introductionmentioning
confidence: 99%